Perubahan Fasilitas Perpustakaan Terhadap Minat BacaSiswa Di OKU Timur Sumatera Selatan - Marina Malian (LKP KARYA PRIMA KURSUS, 2025)
In South Sumatra Province, specifically in East OKU, only PAUD and Elementary School level educational facilities are available. There is no middle school or high school; The increasing level of education after elementary school means that many elementary school students in East OKU are not interested in continuing to the next level because of the distance and costs they have to travel to get to their target school. Therefore, students' interest in reading is reduced, especially because school library facilities and infrastructure are inadequate. The method used is an individual approach carried out in groups into three parts (timedu-support, motivation team, and counseling guidance team). Several results were found from three aspects: (1) Motivation Team, found differences in students' levels of interest in learning; (2) Extension Team, forming a youth organization to mobilize East POKU community activities, such as competitions, regular recitations, mutual cooperation, and so on; (3) Edu Support Team, repairing 3 educational facilities, namely the school library, village reading park and multi-purpose field.